The Scope of Pediatric Physical Therapy Practice in Health Promotion and Fitness for Youth With Disabilities. Issue 1 (2015) - Rowland, Jennifer L.; Fragala-Pinkham, Maria; Miles, Cindy; O'Neil, Margaret E.
Abstract : Purpose: The purpose of this report is to discuss the scope of pediatric physical therapy practice in health promotion and fitness for youth with disabilities. Summary of Key Points: Evidence is provided that supports integration of health promotion and fitness strategies in physical therapy clinical management. Physical therapists' roles in community-based adapted sports and fitness interventions and reimbursement considerations are discussed. Conclusions: Physical therapists are in a unique position to provide expertise in the design and implementation of health promotion and fitness programs for youth with disabilities. These programs are important to promote active, healthy lifestyles and reduce comorbidities associated with sedentary behaviors and unhealthy weight, which are often seen in youth with disabilities. Recommendations for Clinical Practice: Pediatric physical therapists should incorporate health promotion and fitness strategies into practice. Abstract : This Section on Pediatrics task force, formed to describe the scope of pediatric PT in health promotion, recommends the incorporation of health promotion and fitness strategies into practice.